Mastering English Through Global Debate - Talalakina, Ekaterina (Mastering Languages Through Global Debate Ser., 2014)
Mastering English through Global Debate brings together the rhetorical traditions and the best practices of ESL instruction to facilitate superior-level proficiency in the English language. Each chapter addresses a topic of debate, providing students with materials that foster the language and critical thinking skills needed for successful debates.